UMPSA achieves MS ISO 9001:2015 Certification, Demonstrating Excellence in Governance - Nor Salwana, Mohammad Idris (UMPSA, 2024)
KUANTAN, 18 December 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has successfully attained the MS ISO 9001:2015 certification, further proving the university’s excellence in governance and the delivery of high-quality public services.